The student's guide to writing : spelling, punctuation and grammar - Peck, John, 1947- (Palgrave study skills., 2012)
In response to the criticism that few students are taught the basic rules of English at school, this book shows college and university students how to improve their essay writing skills and their command of grammar, spelling and punctuation.